O-238 Preterm birth after recurrent pregnancy loss: A systematic review and meta-analysis. (6th August 2021) - Wu, C; Nichols, K; Carwana, M; Nicholas, C; Maratta, C
Abstract: Study question: What is the impact of recurrent pregnancy loss on the risk of preterm birth? Summary answer: Women with RPL were found to be at increased odds of having preterm deliveries (<37 weeks gestation) in their subsequent live pregnancies. What is known already: Recurrent pregnancy loss (RPL) occurs in up to 5% of all women with miscarriages. The emotional, physical, and financial burden associated with RPL is unequivocal, and over the years, much research has gone into the management of RPL. However, relatively little is known about the perinatal outcomes following RPL. Past research in the area reports conflicting data on the association between RPL and preterm birth (PTB) in a subsequent pregnancy. Study design, size, duration: A systematic search was performed across thePubMed, EMBASE and Google Scholar databases for relevant studies published up until October 2020. Observational cohort and case-control studies comparing the risk of preterm birth (PTB) among women with and without a history of RPL were included. Effect estimates were pooled using a DerSimonian and Laird random-effects meta-analysis model. Study appraisal was performed using the Newcastle-Ottawa scale. Participants/materials, setting, methods: We included studies where the study population consisted of women with a history of RPL (defined as 2 or more pregnancy losses), where the comparator group consisted of women without a history of RPL, and where the outcomes assessed included PTB (defined as birth prior to 37 completed weeks gestation). Two reviewers independently extracted data in duplicate. Publication date, population, exposure and outcome data were extracted. Main results and the role of chance: A total of 12 retrospective observational studies met inclusion criteria, and were included in the systematic review and meta-analysis (N = 37, 046 women with a history of RPL). Incidence of PTB among the RPL groups ranged from 5.8% to 19.6%, and from 1.5-14.0% in the non-RPL groups. A pooled OR of 1.59 with 95% CI 1.40-1.80 was observed in our random-effects meta-analysis with an I 2 of 84%. Subgroup analyses were completed for the pooled risk of only 2 RPL (pooled odds ratio [OR] 1.35; 95% CI 1.08-1.69; I 2 =84.7%); ≥2 RPL (pooled OR 1.42; 95% CI 0.91-2.22; I 2 =68.9%); and ≥3 RPL (pooled OR 1.86; 95% CI 1.51-2.29; I 2 =79.5%). Limitations, reasons for caution: Inconsistent adjustment for confounders and significant between-study heterogeneity were noted in this study. Wider implications of the findings: Despite significant heterogeneity among studies, we found that women with a history of RPL had significantly higher odds of delivering preterm infants in their subsequent pregnancies. Trial registration number: CRD 224763